2010
DOI: 10.1007/s11033-010-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

The association of polymorphisms in DNA base excision repair genes XRCC1, OGG1 and MUTYH with the risk of childhood acute lymphoblastic leukemia

Abstract: The aim of this study was to evaluate the association of polymorphisms in genes encoding three key proteins of DNA base excision repair (BER): the OGG1 Ser326Cys, the MUTYH Tyr165Cys and the XRCC1 Arg399Gln with the risk of childhood acute lymphoblastic leukemia (ALL). Our study included 97 children patients with ALL (mean age 5.4±2.5) and 131 healthy children (mean age 6.2±2.8) used as controls. Genetic polymorphisms in BER pathway genes were examined using PCR and restriction fragment length polymorphism (RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 26 publications
0
26
1
Order By: Relevance
“…NSCLC patients have different prognoses within the same stage, suggesting that treatments should differ based on individual genetic backgrounds. Previous studies demonstrated that polymorphic changes within several DNA repair genes may be functional and are associated with the risk of various cancers (Krupa et al, 2009;Stanczyk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC patients have different prognoses within the same stage, suggesting that treatments should differ based on individual genetic backgrounds. Previous studies demonstrated that polymorphic changes within several DNA repair genes may be functional and are associated with the risk of various cancers (Krupa et al, 2009;Stanczyk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 8-oxoguanine DNA glycosyslase (OGG1) gene encodes a DNA repair protein that removes 8-oxo-7,8-dihydroguanine (8-oxoG) [6]. The variant allele of the Ser326Cys polymorphism is associated with higher level of genetic instability and seems to be associated with an increased risk of lung, esophagus, prostate cancer as well as ALL (acute lymphoblastic leukemia) among children [7][8][9]. Opinion is divided as to whether there is an association between OGG1, Ser326Cys and colorectal cancer [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated a role of the HOGG1 Ser326Cys polymorphism in many cancers including oro-laryngeal cancer (Elahi et al, 2002;Yang et al, 2008), esophageal cancer (Xing et al, 2001), lung cancer (Lan et al, 2004), gastric cancer (Hanaoka et al, 2001), renal cell carcinoma (RCC) (Zhao et al, 2011), gallbladder cancer (Jiao et al, 2007), bladder cancer (Arizono et al, 2008), prostate cancer (Zhang et al, 2010) and acute lymphoblastic leukemia (Stanczyk et al, 2011).…”
mentioning
confidence: 99%